Analyzing of Grammatical Errors Found in Students’ Recount Text - Farisya Rizkah Rachman; I Gusti Bagus Wahyu Nugraha (CV Wahana Publikasi, 2024)
This research aims to identify grammatical errors in using the past tense of eleventh students of SMA Dharma Praja Denpasar in writing recount text. In this study, the researcher obtained data by direct field observation. The data were taken from recounted text writing made by eleven-grade students of SMA Dharma Praja, 30 of whom were involved in this study. The population of this study only took one eleventh-grade class, namely XI MIPA 1. The data was the student’s original writing without the help of Google Translate during the writing process. This study used the theory proposed by Dulay et al. (1982) to analyze the types of grammatical errors. The method used for this study is the descriptive qualitative method to analyze the data. The total number of errors made by students can be seen from the data that has been analyzed. The highest error frequency was misformation and misinformation, with 45 errors (1.5 %). The second was the omission error, with 21 (0.7%). Then, the third error was addition, with a total error of 13 (0.43%). The last was misordering, which only found five errors (0.16%). This error occurred because students still do not understand proper grammar. Therefore, the language that has been written is still very influenced by the pattern of using their mother language and their everyday language.